The impact of centralized electronic bidding system on procurement prices for generic medicines: A case study from Thailand - Amarawan Pentrakan; Jiun-Yi Wang; Wing-Keung Wong (Songklanakarin Journal of Science and Technology (SJST), 2022)
A centralized electronic bidding (e-bidding) system has recently become a key government strategy in developing mechanisms for public drug purchasing systems in Thailand. From the previous literature, e-bidding can be an effective tool for controlling the purchase price of a product in various industries. However, this system is still uncommon in pharmaceutical procurement. Thus, this study aims to determine the impact of the e-bidding system on the pricing of generic medicines. Drug procurement data from Thailand for all generic products of omeprazole injection from 2018 to 2019 were used to analyze drug price changes before and after the adoption of the e-bidding system. The results showed that the effect of the e-bidding system was consistent with a 17.35% drop in the mean prices. In addition, the distribution of purchase prices was greatly reduced compared to the traditional system.